Prototype Development of Myoelectrics Signal-Based Exoskeleton - Shabrine, Anggrian Riska Amelia; Pujiyanto, Pujiyanto; Rahmatillah, Akif (Universitas Airlangga, 2021)
Diffable is incompleteness or abnormality accompanied by consequences for specific functions. The method used is tapping on the hamstring and hamstring muscles quadriceps to determine the resulting voltage”muscle signal tapping using Electromyograph (EMG) and Ag-AgCl electrodes. Average current-voltage contraction and relaxation are used as threshold values to drive the servo motor. This study indicates the tension when the muscle contracts are in the range of 4 volts while the relaxation time is 0.4 volts. Then it can be concluded that the voltage when the muscle is contracted is more significant than when it is relaxed. Using different tension during contraction and relaxation in normal subjects showed that the different tension could drive the prototype exoskeleton.